Gamificação no ensino de ciências : perspectivas e desafios para os professores do ensino fundamental II em escolas públicas no município de Manaus-Am - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
In contemporary times, involvement with games, whether board, card, console or digital, is common among children, young people and adults. Gamification, which incorporates attractive elements of games, has stood out in education. At the school level, challenges are launched to teachers to create game structures in their teaching methodologies, stimulating student interest and engagement. In Science teaching, gamification offers an enriching and dynamic approach, promoting content learning and critical thinking. The objective is to investigate the perception of Science teachers in the Final Years of Elementary School about gamification as a pedagogical resource. The research is qualitative in nature. As instruments we used a bibliographic review and the application of a questionnaire using the Google Forms platform. In the review, 12 studies were found, including articles and dissertations, with a survey carried out on the BDTD and CAPES platforms. In turn, the research adopted a survey approach, with descriptive characteristics and a predominance of qualitative elements. The locus is on the city of Manaus, Amazonas, in collecting responses from 28 teachers who work with Science content in public schools. Data analysis adopted the coding and categorization technique of Bardin (2016). Our results emphasize that the use of gamification in teaching and learning strategies favors student motivation, providing playful training opportunities, based on collaborative and critical work. However, many challenges are involved in this articulation, such as the lack of structure in schools, the inexperience of teachers when dealing with technologies in teaching, deconcentration, leading to loss of focus and frustration in the activities carried out, among other elements. We indicate the importance of diversifying teaching and learning methodologies, based on increased public investments to provide adequate infrastructure, continued training to equip teachers and disseminate innovative methodologies in the (re)organization of curricula and assessment of performance. The research contributes to the understanding of pedagogical practices in the context of Information and Communication Technologies (ICT) and gamification in science teaching, favoring critical teaching based on teacher mediation and the search for student autonomy.
Gamification in science teaching: perspectives and challenges for Elementary School II teachers in public schools in the city of Manaus - AM
Keywords: .; .; .; CIENCIAS HUMANAS; Gamificação; Ensino de Ciências; Educação; Metodologias ativas; Percepção docente